The Summer I Turned Pretty - Han, Jenny (New York Penguin Books, 2009)
Everything that happened this past summer, and every summer before it, has all led up to this. To now. Every year Isabel spends a perfect summer at her family friends' house. There's the swimming pool at night, the private stretch of sandy beach ... and the two boys. Unavailable, aloof Conrad - who she's been in love with forever - and friendly, relaxed Jeremiah, the only one who's ever really paid her any attention. But this year something is different. They seem to have noticed her for the first time. It's going to be an amazing summer - and one she'll never forget ...
Keywords: Friendship -- Summer -- Interpersonal relations